WINTER HARDINESS OF REPRESENTATIVES OF THE GENUS Allium L. IN THE MOSCOW REGION, DEPENDING ON THE SEVERITY OF THE WINTER PERIOD - A. V. Soldatenko; М. I. Ivanova; A. F. Bukharov; A. I. Kashleva; D. N. Baleyev; O. A. Razin (Овощи России)
In the Moscow region, for a long-term species of bows in winter, a complex of limiting factors determines their winter hardiness. To characterize the period from November to March 2014-2017. The winter severity index (Woz) was calculated on a scale from 0 to 10 points (0 very soft, 10 very severe). The severity of winter in 2014-2015 was 2.91 points, 20152016 3.14 points, 2016-2017 4.75 points. The average percentage of overwintered plants for each sample was determined by the ratio of the number of living plants to the number of dead. Many varieties of welch onion were not sufficiently winter-hardy, including Red, Snowdrop, Russian size, Handsome, April, Russian winter. Stable high 100% winter hardiness showed a variety of welch onion Green feathers. From the studied 71 species and 194 samples of bows of perennial different ecological and geographical origin under the conditions of the Moscow region in the subgenus Amerallium plants A. neapolitanum Cirillo (Molium section) and A. ursinum L. (section Arctoprasum), and also in the subgenus Nectaroscordum A. bulgaricum plants (Janka) Prodбn (section Nectaroscordum (Lindl.) Gren. & Godr.) in the winter of 2014-2015 died completely. Winter in 2016-2017 years in the subgenus Rhizirideum, section Rhizirideum G. Don ex Koch A. senescens L. plants overwintered 75%, A. nutans L. – 90-95% depending on the sample, A. stellarianum Willd. 15 %. In subgenus Melanocrommyum, section Melanocrommyum Webb & Berthel. s.s. plants A. cyrillii Ten. overwintered 75%. In the subgenus Butomissa, sections Butomissa (Salisb.) Kamelin plants Allium odorum L. overwintered 86-93% depending on the sample. In the subgenus Cepa, the section Schoenoprasum Dum. plants A. ledebourianum Schult. & Schult. f. overwintered 75%. The remaining species overwintered 100%.